Just how good is unemployment as a measure of welfare? A policy note - Emmanuel S. de Dios; Katrina Dinglasan (University of the Philippines, School of Economics (UPSE), 2014)
The government is rightly concerned with employment generation to make growth inclusive. The use of the open unemployment rate to measure its success, however, is misplaced. In a developing country with a large informal sector and in the absence of unemployment insurance, open unemployment is primarily a middle-class phenomenon: the unemployed are not predominantly poor, and the poor are not predominantly unemployed. Measures of productivity and shifts of labour across sectors may contain more information.
Keywords: J21; I32; 330; unemployment; underemployment; labour force; welfare; poverty